Effect of N Fertilization Pattern on Rice Yield, N Use Efficiency and Fertilizer–N Fate in the Yangtze River Basin, China - Liu, Xiaowei; Wang, Huoyan; Zhou, Jianmin; Hu, Fengqin; Zhu, Dejin; Chen, Zhaoming; Liu, Yongzhe (PloS one, 2016)
High N loss and low N use efficiency (NUE), caused by high N fertilizer inputs and inappropriate fertilization patterns, have become important issues in the rice (Oryza sativa L.) growing regions of southern China. Changing current farmer fertilizer practice (FFP, 225 kg ha-1 N as three applications, 40% as basal fertilizer, 30% as tillering fertilizer and 30% as jointing fertilizer) to one-time root-zone fertilization (RZF, 225 kg ha-1 N applied once into 10 cm deep holes positioned 5 cm from the rice root as basal fertilizer) will address this problem. A two-year field experiment covering two rice growing regions was conducted to investigate the effect of urea one-time RZF on rice growth, nutrient uptake, and NUE. The highest NH4+-N content for RZF at fertilizer point at 30 d and 60 d after fertilization were 861.8 and 369.9 mg kg-1 higher than FFP, respectively. Rice yield and total N accumulation of RZF increased by 4.3-44.9% and 12.7-111.2% compared to FFP, respectively. RZF reduced fertilizer-N loss by 56.3-81.9% compared to FFP. The NUEs following RZF (mean of 65.8% for the difference method and 43.7% for the labelled method) were significantly higher than FFP (mean of 35.7% for the difference method and 14.4% for the labelled method). In conclusion, RZF maintained substantial levels of fertilizer-N in the root-zone, which led to enhanced rice biomass and N uptake during the early growth stages, increased fertilizer-N residual levels and reduced fertilizer-N loss at harvest. RZF produced a higher yield increment and showed an increased capacity to resist environmental threats than FFP in sandy soils. Therefore, adopting suitable fertilizer patterns plays a key role in enhancing agricultural benefits.